Arduino-Based Smart Dustbin with Ultrasonic Sensor for Efficient Waste Management - Faisal Shaharil, Muhamad Haikal; Ahmad Po'ad, Farhana (Evolution in Electrical and Electronic Engineering, 2024)
The invention of the Arduino-based smart dustbin equipped with several sensors aims to improve waste management system efficiency by automating and user-friendly processes. The goal of this project is to create a smart dustbin that can automatically open its lid when someone approaches, monitor and tell the user about the trash level, weigh the waste, and detect dangerous gases to maintain a safe atmosphere. The integration of these functionalities is intended to promote hygiene, increase trash collection efficiency, and improve safety. The scope of this project encompasses the design, development, and testing of a smart dustbin using various sensors including an ultrasonic sensor, IR sensor, load cell sensor, and MQ-2 air quality sensor. The system is also integrated with the Blynk app, allowing users to receive real-time notifications. The project is intended for usage in both household and small commercial settings. The experimental findings showed that the ultrasonic sensor reliably recognized the presence of people within a 30 cm range, effectively actuating the lid. The IR sensor accurately monitored trash levels and successfully provided notifications. The load cell sensor gave accurate weight measurements with minimum error, while the MQ-2 air quality sensor detected dangerous chemicals and activated the alert as planned. The Arduino-based smart dustbin successfully integrates several sensors, resulting in an automated and intelligent trash management solution.